Византийская поливная керамика VII – первой половины IX вв. из раскопок Мангупа - Смокотина, А.В. (Материалы по археологии, истории и этнографии Таврии, 2003)
Настоящая работа посвящена публикации коллекции фрагментов ранней византийской поливной посуды VII - первой половины IX вв., полученной в ходе изучения цитадели Мангупа с конца 70-х гг. XX вв. до настоящего времени^. Присутствие згой группы византийского импорта на городище представляется достаточно важным для характеристики торгово-экономических связей Дороса в чрезвычайно сложный период его политической истории, который нередко в специальной литературе обозначается термином “темные века” . Тезис о сохранении традиционных контактов с Византией, при посредничестве Херсона - одного из ключевых пунктов в зоне “византийско-хазарского пограничья” в горной Таврике, получает, безусловно, дополнительные материальные свидетельства. This work is devoted to the publication of a small collection of early Byzantine glazed ceramics dating back to the 7th - the first half of the 9th centuries (Group “Glazed White Ware I” according to J. W. Hayes) from the excavations in the citadel of Mangup and a prospecting shaft on the southern slope of Teshkiy-burun cape. The description of the vessels in the form of a catalogue completed with the data on stratigraphic location of the wares and selection of analogies from the published complexes of that period. Rather scanty knowledge about crockery of GWW I and small quantity of its production and spread on the territory of Byzantium brought to the necessity of the analysis of general problems of chronology, morphological and technological criteria to single out this group of ceramics. Revelation of Byzantine ceramic import in the 7th - the first half of the 9th centuries in Mangup seems to be very important for characteristics of trade - economic relations of the settlement and is an additional material evidence of maintaining traditional contacts with Cherson and city centers of Byzantine Empire in that period.